EDUKASI BENCANA NON ALAM DENGAN DONOR DARAH UNTUK MASYARAKAT DESA PARUNGSEAH - Nadia Mayla Anggraeni; Mira Nurkamila; Mega Laelasari; Abdurrahman Abdurrahman Al-Ansori; Abdul Manaf; Wildan Nurhakim (Jurnal Sosio dan Humaniora (SOMA), 2023)
Blood donation is the process of taking blood from someone voluntarily to be stored in a blood bank for later use in blood transfusions. Blood donor selection is carried out with the aim of protecting the health of donors by ensuring that the donation is not harmful to their health, and protecting patients from the risk of infectious diseases or other adverse effects. So far, PMI often experiences critical conditions, namely the lack of safe blood supplies needed by the community. The benefits of blood donation for regular donors can help stimulate the production of new blood cells, therefore our goal is to educate the public to convey the importance of blood donation for body health.